Adverse events among pulmonary drug-resistant tuberculosis patients in Banten, Indonesia - Restinia, Mita; Siddiqa, Alyya; Sari, Wulan Purnama (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Drug-resistant Tuberculosis (DR-TB) treatment requires an extended duration, making adverse events (AEs) a common concern. This study aimed to assess the frequency of AEs, time to events, and their association with treatment outcomes among DR- pulmonary TB patients. A retrospective cohort study was conducted on patients aged >18 years at one of public hospitals at Tangerang, Banten, Indonesia, from March 2021 to May 2023. Bivariate analysis was used to analyze the association between AEs and treatment outcomes. Among 53 patients included in the study, all experienced at least one AEs. Number of AEs mean ± SD; 9.724±4.86. Mild AEs were reported in 100% of patients, while 75.5% experienced moderate AEs, and 81.1% experienced severe AEs. The most common AEs included nausea (90.6%), anemia (73.6%), vomiting (62.3%), decreased appetite (60.4%), and joint pain (60.4%). The AEs were frequently reported during intensive phase (4-6 months). AEs have association with treatment outcome (P<0.05). The frequency of AE among DR-TB patients was high. Early detection and effective management of AEs are essential to improving treatment outcomes for DR-TB patients.